Construction of Optically Active 2H‐ and 3H‐Pyrroles by Cyclization and Chirality Maintaining 1, 5‐Ester Shift Reactions. Issue 16 (5th July 2019) - Li, Dan; Wang, Linqing; Yang, Yuling; Zhang, Minmin; Peng, Tianyu; Yang, Dongxu; Wang, Rui
Abstract: Construction of enantioenriched 2 H ‐ and 3 H ‐pyrroles are achieved in current work by using readily available α‐isocyanoacetates and alkynyl ketones as precursors. To realize the asymmetric synthesis of 2 H ‐pyrroles, a proper in situ generated magnesium catalytic method was developed. On the other hand, the discovery of an aluminium mediated chirality maintaining 1, 5 ‐ester shift reaction promoted the successful synthesis of enantioenriched 3 H ‐pyrroles. Abstract :